2020
DOI: 10.1103/physrevmaterials.4.094404
|View full text |Cite
|
Sign up to set email alerts
|

Impact of impurities on the spin Hall conductivity in β -W

Abstract: While the metastable β (A15) phase of tungsten has one of the largest spin Hall angles measured, the origin of this high spin Hall conductivity is still unclear. Since large concentrations of oxygen and nitrogen are often used to stabilize β tungsten, it is not obvious whether the high spin Hall conductivity is due to an intrinsic or extrinsic effect. In this work, we have examined the influence of O and N dopants on the spin Hall conductivity and spin Hall angle of β-W. Using multiple first principles approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 57 publications
2
5
0
Order By: Relevance
“…[ 13–15 ] Even though, part of such variation can be attributed to different experimental techniques [ 14 ] and the use of different models for data analysis, such a high degree of discrepancy requires deeper probing. On the other hand, the theoretical studies show much better consistency with σ SH for β‐W ≈ 1500–2000 ℏ/e S cm −1 as reported by various groups [ 16,17 ] and can be used as a benchmark.…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…[ 13–15 ] Even though, part of such variation can be attributed to different experimental techniques [ 14 ] and the use of different models for data analysis, such a high degree of discrepancy requires deeper probing. On the other hand, the theoretical studies show much better consistency with σ SH for β‐W ≈ 1500–2000 ℏ/e S cm −1 as reported by various groups [ 16,17 ] and can be used as a benchmark.…”
Section: Introductionsupporting
confidence: 64%
“…[13][14][15] Even though, part of such variation can be attributed to different experimental techniques [14] and the use of different models for data analysis, such a high degree of discrepancy requires deeper probing. On the other hand, the theoretical studies show much better consistency with σ SH for β-W ≈ 1500-2000 ℏ/e S cm −1 as reported by various groups [16,17] and can be used as a benchmark.In the first part of this work, we focus on minimizing the growth and fabricationrelated uncertainties and carry out systematic characterization of SOT using the anomalous Hall harmonics analysis method. [18] We perform in-depth analysis considering various factors and conform our experimentally extracted parameters with the same evaluated using the ab initio method to establish a robust protocol.…”
supporting
confidence: 60%
“…Therefore, the intrinsic spin Hall effect in W─Ta─B may originate from the short-range order of the 𝛽-phase W. In Figure 3d, we also observed an increase in |𝜉 E SHE | (|𝜉 Our interpretation is that the enhancement of the spin Hall effect originates from the effect on the Fermi-level tuning of W by Ta substitutional doping. [27][28][29]49,50] According to the first-principles calculation for 𝛽-W, the spin Hall effect based on the intrinsic mechanism shows a maximum at 0.4-0.5 eV below the Fermi level. [27][28][29] Substitutional doping of Ta into W corresponds to effective hole doping.…”
Section: Spin-orbit Torque Efficiency and Spin Hall Effectmentioning
confidence: 99%
“…Typical candidate materials with large spin Hall angles are Pt (or its binary alloys), [16][17][18] 𝛽-phase W (𝛽-W), [19][20][21][22][23] 𝛽-phase Ta (𝛽-Ta), [6] and topological insulators. [24,25] All these materials have polycrystalline (textured) or single-crystal structures, in which a large spin Hall effect is theoretically expected by an intrinsic mechanism based on the band structure of materials with long-range crystal order [26][27][28][29] . As a result of extensive experimental studies, some such materials exhibiting large spin Hall angles have been observed, and with these j c0 < 1 × 10 7 A cm −2 could be achieved [30][31][32][33][34][35] .…”
Section: Introductionmentioning
confidence: 99%
“…The code has been employed in multiple areas of materials science since its initial release in 2016. In particular, several groups used it to compute the (spin) Berry curvature as well as spin and/or anomalous Hall conductivity (SHC and AHC) in a variety of materials, ranging from β-W to magnetic antiperovskites [4][5][6][7][8]. Transport quantities, such as the electrical and thermal conductivity, were also computed in order to analyze carrier mobility in thermoelectrics [9,10].…”
Section: Introductionmentioning
confidence: 99%